Narratives in economics - Michael W. M. Roos; Matthias Reccius (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
There is growing awareness within the economics profession of the important role narratives play in the economy. Even though empirical approaches that try to quantify economic narratives are getting increasingly popular, there is no theory or even a universally accepted definition of economic arratives underlying this research. First, we review and categorize the economic literature concerned with narratives and work out the different paradigms that are at play. Only a subset of the literature considers narratives to be active drivers of economic activity. In order to solidify the foundation of narrative economics, we propose a definition of collective economic narratives, isolating five important characteristics. We argue that, for a narrative to be economically relevant, it must be a sense-making story that emerges in a social context and suggests action to a social group. We also systematize how a collective economic narrative differs from a topic and from other kinds of narratives that are likely to have less impact on the economy. With regard to the popular use of topic modeling as an empirical strategy, we suggest that the complementary use of other canonical methods from the natural language processing toolkit and the development of new methods is inevitable to go beyond identifying topics and be able to move towards true empirical narrative economics. – – In den Wirtschaftswissenschaften wächst das Bewusstsein für die wichtige Rolle, die Narrative in der Wirtschaft spielen. Obwohl empirische Ansätze zur Quantifizierung ökonomischer Narrative immer beliebter werden, gibt es keine Theorie oder gar eine allgemein akzeptierte Definition von wirtschaftlichen Narrativen, die dieser Forschung zugrunde liegen. Zunächst sichten und kategorisieren wir daher die ökonomische Literatur, die sich mit Narrativen beschäftigt, und arbeiten die zugrunde liegenden Paradigmen heraus. Nur eine Teilmenge der Literatur betrachtet Narrative als aktive Triebkräfte der Wirtschaftstätigkeit. Um das Fundament der narrativen Ökonomik zu festigen, schlagen wir eine Definition kollektiver ökonomischer Narrative vor und isolieren fünf wichtige Merkmale. Wir argumentieren, dass ein Narrativ nur dann wirtschaftlich relevant ist, wenn es eine sinnstiftende Geschichte ist, die in einer sozialen Umgebung entsteht und eine soziale Gruppe zum Handeln animiert. Wir systematisieren auch, wie sich ein kollektives ökonomisches Narrativ von einem Thema und anderen Arten von Narrativen unterscheidet, die wahrscheinlich weniger Einfluss auf die Wirtschaft haben. Im Hinblick auf die populäre Verwendung der Themenmodellierung als empirische Strategie schlagen wir vor, dass die ergänzende Verwendung anderer kanonischer Methoden aus dem Werkzeugkasten der Computerlinguistik und die Entwicklung neuer Methoden unumgänglich sind, um über die Identifizierung von Themen hinauszugehen und sich in die Richtung echter empirischer narrativer Ökonomik zu bewegen.
Keywords: D91; E44; E71; B55; B41; 330; Narrative economics; complexity economics; narrative turn; textual analysis; NLP